Application of finger-pressing on Tiantu acupoint to induce cough in postoperative patients with early-stage lung cancer (指压天突穴引咳法在早期肺癌术后患者中的应用) - BIAN Guanjun (边冠军); ZHANG Chunmei (张春梅); LIU Lifeng (刘丽峰) (中西医结合护理)
Objective To investigate the application of finger-pressing on Tiantu acupoint to induce cough in postoperative patients with early-stage lung cancer. Methods Totally 100 patients with peak expiratory flow (PEF) ≤5. 33L/s who were admitted to the Hospital from January 2023 to March 2023 were randomly divided into observation group and control group, with 50 cases in each group. The control group received conventional nursing measures, while the observation group received finger-pressing therapy on Tiantu acupoint based on the basis of the control group. The time taken to cough up the first sputum after nebulization on the first postoperative day, the difference of Peak Expiratory Flow (PEF) on first day of hospital admission and three days after surgery, postoperative pulmonary complications and intervention effect on coughing were compared between the two groups. Results The rate of effective cough-inducing in the observation group was significantly higher than that of the control group(P＜0. 01). The time (h) to cough up the first sputum after nebulization on the first postoperative day was shorter in the observation group (1. 73±0. 81) than in the control group (3. 02±0. 88), with a significant difference(P＜0. 01). The incidence of postoperative pulmonary complications in the observation group was lower than that in the control group (P＜0. 01). The rank of the difference of PEF on first day of hospital admission and three days after surgery was lower in the observation group than that in the control gorup(P＜0. 05). Neither of the groups reported adverse reactions. Conclusion Finger-pressing therapy on Tiantu acupoint to induce coughing is effective in coughing and sputum evacuation in early-stage lung cancer patients with PEF ≤ 5. 33 L/s, and reduces pulmonary complications. (目的 探讨指压天突穴引咳法在早期肺癌术后患者中的应用。方法 便利抽样法选取天津市某三级甲等肿瘤专科医院肺部肿瘤科2023年1月—3月收治的100例呼气峰值流速(PEF)≤5. 33L/s的早期肺癌切除术的患者, 随机分为观察组和对照组, 各50例。对照组接受常规护理措施, 观察组在对照组基础上实施指压天突穴引咳法干预。比较两组患者术后第1天雾化后咳出第一口痰的用时、术后3 d晨起PEF与入院PEF差值、肺部并发症发生情况和咳痰效果。结果 观察组咳痰效果评价优于对照组, 差异有统计学意义(P＜0. 01)。观察组术后第1天雾化后咳出第一口痰用时(1. 73±0. 81)h, 较对照组(3. 02±0. 88)h缩短, 差异有统计学意义(t=3. 447, P＜0. 01)。观察组肺部并发症发生率低于对照组, 差异有统计学意义(P＜0. 01)。观察组入院及术后第3天晨起的PEF差值的秩均值小于对照组(P＜0. 05)。两组均未出现严重或者影响机体状态的不良事件。结论 指压天突穴引咳法在PEF≤5. 33L/s的早期肺癌术后患者咳嗽排痰中应用效果明显。)